A methodology for modeling healthcare teams and an evaluation of Business Process Modeling Notation as a Modeling Language - Ojo, Tolulope A. (Université d'Ottawa / University of Ottawa, 2012)
Whether it is offering services, delivering solutions or driving innovations, team work has been a hallmark of efficiency and effectiveness in various industries. The healthcare industry is not left out as its service delivery process involves numerous interfaces, information flows and patient hand-offs among professionals with different educational training, differing knowledge levels and possibly working from different locations as well. As healthcare delivery evolves to being more patient-centered, so does the team settings as well, becoming more collaborative. Such changes also translate into a need for support systems to evolve to be able to provide support for the extent of collaboration that would be needed. A framework is needed to guide in the development of such systems. However, due to the varying needs of patients, team types and make-up would generally differ, so we explored the different types of team settings studying what they entail based on their various degrees of collaboration. We therefore present in this thesis a model of team based concepts, an ontology formalizing the model, team based scenarios designed using the ontology and then application of the scenarios to test the ability of BPMN (Business Process Modeling Notation) to model healthcare teams.
Keywords: Healthcare teams; Methodology; Mind map for healthcare teams; Ontology for healthcare teams; Interdisciplinary teams in healthcare; Multidisciplinary teams in healthcare; Healthcare team types; Healthcare team processes; Reference model for healthcare teams; Business process modeling in Healthcare; BPMN and healthcare team types; IT for Healthcare; Teamwork; Collaboration in healthcare; Team based care delivery; Patient-centred care; Information Systems in Healthcare; Business analysis in healthcare; Process analysis in healthcare; Model for healthcare teams; Information needs in healthcare; Teamwork in complex sectors; Improving info. sys. in healthcare; Methodology for modeling teams; Composition of healthcare teams; IT and info. systems in healthcare; Info. systems in healthcare; Modeling in team based environments; Team concepts in healthcare; Framework for modeling healthcare teams